Potential impact of antimicrobial resistance in wildlife, environment and human health - Radhouani, Hajer; Silva, Nuno; Poeta, Patrícia; Torres, Carmen; Correia, Susana; Igrejas, Gilberto (Frontiers in Microbiology, 2014)
Given the significant spatial and temporal heterogeneity in antimicrobial resistance distribution and the factors that affect its evolution, dissemination and persistence, it is important to highlight that antimicrobial resistance must be viewed as an ecological problem. Monitoring the resistance prevalence of indicator bacteria such as Escherichia coli and enterococci in wild animals makes it possible to show that wildlife has the potential to serve as an environmental reservoir and melting pot of bacterial resistance. These researchers address the issue of antimicrobial-resistant microorganism proliferation in the environment and the related potential human health and environmental impact.